Microbial degradation of organic carbon sorbed to phyllosilicate clays with and without hydrous iron oxide coating. (14th October 2014) - Saidy, A. R.; Smernik, R. J.; Baldock, J. A.; Kaiser, K.; Sanderman, J.
Summary Sorption of organic carbon (OC) to phyllosilicate clays and hydrous iron oxides retards its mineralization, thus contributing to stabilization of organic carbon in soils. The degree of protection varies with the nature of the minerals present. In a previous study, we reported that when the amount of OC exceeds the sorption capacity of minerals, the rate of OC mineralization is determined primarily by mineral surface area. Here, we report on OC mineralization under conditions of less OC loading and with OC pre‐sorbed to the mineral surfaces. The same suite of minerals (kaolinite, illite and smectite with and without goethite coating and illite coated with haematite, goethite and ferrihydrite) was used as in the previous study. The stability of sorbed OC decreased in the order kaolinite > illite > smectite amongst the uncoated clays. Goethite coating of kaolinite and smectite increased the stability of sorbed OM against microbial decomposition, while the stability of illite‐associated OC did not change with goethite coating. For illite coated with different hydrous iron oxides, only ferrihydrite increased the stability of sorbed OC against microbial decomposition. These differences reflect closely the differences in the strength and reversibility of OC sorption, as measured in previous batch sorption experiments on these systems, rather than reflecting differences in mineral surface area. These findings demonstrate that at relatively small loadings of OC, the degree of protection of sorbed OC provided by mineral surfaces is controlled primarily by the strength of organo–mineral associations.